Brain death communication with parents of children and adolescents: care strategies - Neide da Silva Knihs; Lyandra Caroline Feisther; Juliana dos Santos; Rosi Meri da Silva; Sibele Maria Schuantes Paim; Janine Schirmer; João Luis Erbs Pessoa; Maria Lígia dos Reis Bellaguarda (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to identify care strategies developed by professionals from critically ill patients' units in communicating BD with parents of children and adolescents. Methods: an exploratory and descriptive research with a qualitative approach, carried out in two health institutions between October and December 2019, through semi-structured interviews. Data analysis took place through content analysis. Results: twenty-one professionals participated. Three care strategies were identified: actual clinical situation in suspected brain death; sensitizing families to the real clinical situation after brain death diagnosis; and time to assimilate the death information. Final Considerations: the care strategies for communicating brain death to families identified in this study present the possibility of subsidizing health managers in training and support promotion for professionals in care practice. Moreover, they can be incorporated and validated in the care practice of the studied context.